Legal Certainty Analysis Of Land Control In The Ready-To-Build Plot System (KSB) In Batam City (A Study On The Implementation Of The PTSL Program) - Dewi Fitri Saraswati (Faculty of Law, Universitas Negeri Semarang, 2025)
This research analyzes the legal certainty of land tenure in the Ready-to-Build Plot (KSB) system in Batam City, particularly in the implementation of the Complete Systematic Land Registration Program (PTSL). Batam City, as a rapidly developing industrial area and trade center, has unique characteristics in land management under the Land Management Rights (HPL) of BP Batam. The KSB system, developed as an affordable housing solution, still faces legal certainty issues. This empirical juridical research identifies two main problems: the constraints in implementing PTSL to ensure legal certainty of KSB land rights and the roles of BP Batam and the Land Office in resolving these issues. The results show that administrative constraints such as incomplete ownership documents and technical constraints such as mapping problems and land boundaries are major obstacles. Coordination between BP Batam and the Land Office in PTSL implementation still requires strengthening, particularly regarding harmonization of land data. This research recommends simplifying administrative procedures and enhancing institutional synergy to optimize the PTSL program in providing legal certainty for KSB land rights holders in Batam City.